The effect of interscalene brachial plexus block with propofol sedation on preventing perioperative hypothermia during arthroscopic shoulder surgery - Lee, Ji Hye (Korean J Anesthesiol, 2021)
BACKGROUND: Interscalene brachial plexus block (ISBPB) is commonly used with general anesthesia for postoperative pain management in shoulder surgery. This study investigated the incidence of hypothermia and changes in the body temperature in patients undergoing arthroscopic shoulder surgery under ISBPB with propofol sedation. METHODS: This retrospective study enrolled 220 patients who underwent arthroscopic shoulder surgery. Patients were divided into general anesthesia (n = 34) and ISBPB with propofol sedation (n = 186) groups, and medical records were retrospectively compared. In addition, patients from the ISBPB group were further divided according to age (elderly [≥ 65 years], n = 98 vs. young [< 65 years], n = 88), and the incidence of hypothermia and changes in the body temperature were compared. RESULTS: Twenty-seven patients (12.3%) experienced perioperative hypothermia (range: 35.3–35.9℃). The incidence of perioperative hypothermia was 29.4% and 9.1% in the general anesthesia and ISBPB groups, respectively, and there was a significant difference between the two groups (P = 0.002). The incidence of perioperative hypothermia according to age in the ISBPB group was 9.2% and 9.1% in the elderly and young groups, respectively, and there was no significant difference between the two groups (P = 0.983). CONCLUSIONS: The incidence of perioperative hypothermia during arthroscopic shoulder surgery under ISBPB with propofol sedation is lower than that under general anesthesia. Furthermore, when using ISBPB with propofol sedation, the incidence of perioperative hypothermia in elderly patients is similar to that in younger patients.